By Birth or Consent : Children, Law, and the Anglo-American Revolution in Authority - Brewer, Holly, 1964- (Book collections on Project MUSE., 2005)
"In By Birth or Consent, Holly Brewer explores how the changing legal status of children illuminates the struggle over consent and status in England and America. The concept of meaningful consent, as it emerged through religious, political, and legal debates, challenged the older order of birthright and became central to the development of democratic political theory." "As Brewer demonstrates, the legal status of children serves as a clear measure of the changing foundations of political and legal authority from the sixteenth through the eighteenth centuries. Age was central to this shift to a consent-based ideology, which specifically excluded children from the practice of consent." "Brewer's analysis reshapes the debate about the origins of modern political ideology and makes connections between Reformation religious debates, Enlightenment philosophy, and democratic political theory."--Jacket